A Simulated Annealing Algorithm for a two-stage fixed charge distribution problem of a Supply Chain. (7th January 2010) - Balaji, A.N.; Jawahar, N.
This article considers a two-stage distribution problem of a Supply Chain that is associated with a fixed charge. Two kinds of cost are involved in this problem: a continuous cost that linearly increases with the amount transported between a source and a destination, and secondly, a fixed charge, that incurs whenever there exists a transportation of a non-zero quantity between a source and a destination. The objective criterion is the minimisation of the total cost of distribution. A Simulated Annealing Algorithm (SAA) that belongs to heuristic search method is proposed and illustrated. The proposed methodology is evaluated for its solution quality by comparing it with the approximate and lower bound solutions. Thus, the comparison reveals that the SAA generates better solution than the approximation method and is capable of providing solution either equal or closer to the lower bound solution of the problem.